Numerical evaluation of different landfill daily cover in semiarid areas - Jordan. (2015) - Aljaradin, Mohammad; Persson, Kenneth M.
Efficient and suitable daily landfill cover is considered the most important aspect for minimising the negative impact of landfills on the local environment and population, especially in arid and semiarid countries. In this study, numerical model, HYDRUS-2D/3D, was used to investigate the impact of landfill cover type, cover thickness and antecedent water content on the quantity and the rate of contaminant percolation through the Mafraq landfill in Jordan during a 30-year simulation period. Four different cover types (sandy loam, clay loam, silt and clay), three cover thicknesses (0, 50, 100 cm) and two antecedent soil water content values (θi = 0.12 and 0.20 m 3 m −3 ) were simulated. Initial chloride concentration of 665 mg/l which is equal to the measured concentration in Mafraq landfill leachate was used during simulation. Simulation results showed that maximum chloride concentration for different scenarios at all locations within the soil profile during the entire simulation period was less than the chloride concentration in the municipal solid waste (MSW) leachate. In addition, as the landfill cover thickness increases, the concentration of chloride at a certain location decreases. Meanwhile, the time required to reach this location increases. The simulation results also showed that the effect of θi on chloride concentration reduction increases as the cover thickness increases. A cover thickness of 50 cm is suitable in case of low θi .